Термографический метод определения жидкой фазы в газопроводах - Заморий, П. Ю. (ХНУРЭ, 2012)
The possibility of thermographic method application to the estimation of gas-main pipeline liquid phase contamination content level is considered. The gas pipeline with two-phase innage (gas and liquid) thermalphysical model is built. The experimental and calculation data that confirm the principal possibility of thermographic method application to pipeline condensate level control are given. The environment temperature effect on the considered method sensitivity is analyzed
Keywords: газопровод; физика